Numerical model for the stress field ahead of a crack in elastoplastic regime - Pascon, J. P.; Torres, M. A.S. [UNESP]; Baptista, C. A.R.P. (Elsevier, 2019)
Damage-tolerant designs admit the pre-existence of defects and small cracks, which lead to stress redistribution in structural components. The accurate knowledge of the stress field in parts under these conditions is important for damage accumulation analysis and residual life prediction. In this work, a numerical model via finite elements is proposed to determine the stress field ahead of crack tips in a plate under cyclic loading and elastoplastic regime. The analyzed center-cracked plate simulates a M(T) specimen made of 6005-T6 extruded aluminum alloy. From the triple symmetry condition, one eighth of the plate was discretized with tetrahedral solid finite elements of quadratic order. The refinement of the mesh was concentrated around the crack tip region. The cyclic stress-strain curve of the material was experimentally obtained by strain-controlled fatigue tests. With this curve, elastic and plastic parameters have been determined, considering elastoplastic material with isotropic hardening governed by Swift's law. Such a model differs from most usual stress analyses in cracked components, in which the possibility of hardening is not considered. Cyclic loading with ratios R = 0 and R = -1 has been applied from an initial crack of 11 mm in length. The crack growth was imposed by means of a simplified node release scheme. The results showed no significant variation in terms of the equivalent stress, but considerable differences in the equivalent plastic strain. Therefore, the compressive phase in the specimen under R = -1 contributes to increase the equivalent plastic strain, which means that the level of yielding becomes higher even when the specimen is compressed.
Keywords: Aluminum alloys; Fatigue cracks; Finite Element Method; Numerical modelling